Bioenrichment Tepung Pepaya (Carica Papaya) dengan Formulasi Pakan yang Berbeda pada Performa Pertumbuhan Ikan Nila (Oreochromis niloticus) - Simanjuntak, Ricky Febrinaldy (Jurnal Harpodon Borneo, 2018)
Nutrition value and optimum digestibility of feed formulation can support fish growth out. However, most common constraint is low fish growth out caused by feeding that contain high energy but cannot be digested by fish. Papaya is one of producing papain enzyme (protease) which capable of increasing digestibility and feed protein absorption that impact to enhancing fish growth out. The aim of this research is to find out effectiveness bioenrichment of papaya fruit meal formulation for tilapia growth out performance. Research using completely randomized design with five treatments and three replications. Papaya fruit meal with 0, 1.25, 1.75, 2 and 2.25 g/kg concentration of feed formulation given to tilapia during thirty days period. The results showed that, bioenrichment of papaya fruit meal 2.25g/kg became the best concentration when compared other treatments. Feed with addition of papaya fruit meal 2.25gr/kg was able to produce 29.13g of absolute weight, 7.57g spesific weight, 3.35cm absolute length, 2.22cm specific length and 1.16 point of feed convertion ratio value with 60% survival rate during treatment period. Neverthless, analysis of variance of the sixth treatments showed no significant difference from the overall parameters that was observed. Based on results it can be concluded bioenrichment of papaya fruit meal as much as 2.25g/kg of feed become the best formulation for Tilapia growth out performance. Keywords :Bioenrichment, Papaya Meal, Nile Tilapia